MNEs as border-crossing multi-location enterprises: The role of discontinuities in geographic space - Beugelsdijk, Sjoerd; Mudambi, Ram (Journal of International Business Studies, 2013)
Spurred by the classic work of Dunning, MNE location has become the focus of a growing body of research in the field. In this paper we argue that international business (IB) research examining the spatial dimension has serious weaknesses, stemming from its traditional assumption of the country as the location unit of analysis. While border-crossing remains the key research context of IB, placing it within a general spatial framework that recognizes both international and subnational spatial heterogeneity opens up vast new vistas for research. Analyzing MNEs as border-crossing multi-location enterprises allows the researcher to distinguish between (discrete) border effects and (continuous) distance effects and undertake a more fine-grained analysis of location. Within such analysis national borders may appear as qualitative discontinuities in space, that is, points at which spatial heterogeneity changes abruptly. However, subnational spatial heterogeneity is often the characteristic that drives firm strategy as MNEs decide to locate in particular agglomerations and not at random locations within a country. The complex firms that IB scholars study typically include multiple units within the same country, so that a complete analysis requires considering both subnational distance effects as well as international border effects.